1-2-3 : From 2 to 3 - LeBlond, Geoffrey T.; LeBlond, William B.;Berry, Suzanne P. (Osborne : McGraw Hill Education, 1989)
The method of this book, then, is to show, for every new release 3 feature that is introduced, how you might perform a similar function in release 2, if you could perform it at all.
1. An overview of 1-2-3 release 3 -- 2. Hardware and operating system requirements - 3. Compatibility issues -- 4. Multiple worksheets and files -- 5. Function keys -- 6. Ranges -- 7. File operations -- 8. Data management -- 9. Graphics -- 10. Printing -- 11. Functions -- 12. Macros -- 13. Networking 1-2-3 release 3 -- 14. Using add-ins.
Includes index.
Keywords: COMPUTER SCIENCE